Annotated Translation of Marchella FP's "Nanti Kita Cerita tentang Hari Ini" - Sandra Natasya Alif (Jurnal Linguistik Terapan, 2022)
This study presents an annotated translation, elucidating the translator's rationale for selecting specific meanings. The data originates from Marchella FP's novel, "Nanti Kita Cerita Tentang Hari Ini." The research addresses translation challenges and remedies for writer-translators. The objectives are: (1) unveiling issues encountered in source text translation, and (2) proposing solutions for the identified novel challenges. The researcher employs footnotes and comments during the annotated translation, comprehensively analyzing problems using encoding methods for words, phrases, clauses, sentences, and other translation-related issues. Two chapters are translated, yielding 20 problem instances, each elucidated through relevant strategies. The translation employs varied techniques, primarily synonyms and additions. Overcoming obstacles relies on established translation theories, methods, and procedures. The writer navigates translation tool limitations, consulting dictionaries and search engines, like Google. Rigorous research ensures faithful conveyance of meaning to the target audience.